A multi-sector model of relatedness, growth and industry clustering - Bond-Smith, Steven; McCann, Philip (Oxford University Press, 2019)
This article builds an understanding of regional innovation specialisation by developing a multi-sector model with endogenous growth through quality improving innovations and spillovers from related technologies. The model provides an approach to incorporate the relatedness literature within the mainstream theoretical frameworks of endogenous growth and economic geography. Each firm’s technology sector and the location of other firms play a role in each firm’s ability to improve its own technology. As a result, firms prefer to co-locate in technologically compatible clusters. Without relying on scale assumptions, the model for the first time coherently links related variety knowledge spillovers to mainstream urban economic frameworks and demonstrates that clustering is possible in both core and peripheral areas.